Use of Telehealth Among Racial and Ethnic Minority Groups in the United States Before and During the COVID-19 Pandemic - White-Williams, Cynthia; Liu, Xinliang; Shang, Di; Santiago, Jared (Public health reports (1974), 2023)
The COVID-19 pandemic has propelled the use of technology for health care services delivery. Because of inequities in health care and technology access, we investigated the use of telehealth services among racial and ethnic minority groups before and during the COVID-19 pandemic. For this retrospective study, we examined the electronic health records of privately insured patients in the Healthjump database, provided by the COVID-19 Research Database Consortium. We examined 17.98 million unique visit records of 2.93 million patients from March through December 2019 and 22.17 million records of 3.55 million patients from March through December 2020. We conducted a descriptive analysis and used multiple logistic regression to examine differences in the use of telehealth services among 3 racial and ethnic groups: non-Hispanic White, non-Hispanic Black, and Hispanic people. Telehealth visits before and during COVID-19 accounted for 8.3% and 10.9% of total visits, respectively, with a peak of 15.5% in April 2020. Pre-COVID-19, Hispanic patients had a significantly lower monthly utilization rate (5.3%) than non-Hispanic White patients (8.4%, < .001) and non-Hispanic Black patients (10.4%, = .001). During the pandemic study period, Hispanic patients were 41% less likely than non-Hispanic White patients to have a telehealth visit, controlling for age and sex. The likelihood of using telehealth was lower among Hispanic patients than among non-Hispanic White and non-Hispanic Black patients during the pandemic. Culturally sensitive measures are needed to support telehealth use among the Hispanic population.